„Zwierciadło i zwierzyniec pana Mikołaja Reja”, czyli słów kilka o japońskim odkrywaniu literatury polskiej - Splisgart, Tomomi (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Despite the rise in availability, Polish literature is viewed in Japan as exotic and unavailable. An attempt to fill this gap is being undertaken by Tokimasa Sekiguchi who familiarises the Japanese readers with selected aspects of Mikołaj Rej’s writing in an original work entitled Zwierciadło i zwierzyniec pana Mikołaja Reja (Mirror and Preserve by Mr. Mikołaj Rej), published in 2021 in Tokyo. In the course of the book, the author presents carefully selected works by the Polish poet and prose writer of the Renaissance period, complementing the respective fragments with commentary and references to both the history of Poland and the Japanese context. Tokimasa Sekiguchi’s text constitutes a significant contribution to the understanding of Polish culture and history in the land of cherry blossoms.